Assessing the economywide impacts of COVID-19 on Rwanda’s economy, agri-food system, and poverty: A social accounting matrix (SAM) multiplier approach - Aragie, Emerta A.; Diao, Xinshen; Robinson, Sherman; Rosenbach, Gracie; Spielman, David J.; Thurlow, James (International Food Policy Research Institute, 2021)
Rwanda’s response to COVID-19 has been widely praised for its rapid, systematic, and comprehensive approach to containing the pandemic. Although the economic consequences are unavoidable, the country expects to return its economy to its high-growth trajectory as the pandemic subsides. We use economic modeling tools designed to estimate the short-term economywide impacts of the unanticipated, rapid-onset economic shocks of COVID-19 on Rwanda. - Results show that during the six-week lockdown that began in March, Rwanda’s GDP fell 39.1 percent (RWF 435 billion; USD 484 million) when compared to a no-COVID situation in the same period. - Results further show that Rwanda’s GDP in 2020 will be between 12 and 16 percent lower than a predicted no-COVID GDP, depending on the pace of the recovery. The losses in annual GDP are between RWF 1.0 and 1.5 trillion (USD 1.1–1.6 billion). - While GDP for the industrial and services sectors were estimated to have fallen during the lockdown period by 57 and 48 percent, respectively, exemptions of COVID-19 restrictions for the agricultural sector limited the decline in agricultural GDP to 7 percent compared to a noCOVID situation. - During the lockdown period, the national poverty rate is estimated to have increased by 10.9 percentage points as 1.3 million people, mostly in rural areas, fell into temporary poverty. Poverty rates are expected to stabilize by the end of 2020, increasing only by between 0.4 and 1.1 percentage points. While these figures may be encouraging, they mask the impacts on poor households of the sharp poverty spike during the lockdown and the inherent complexity of poverty dynamics post-lockdown. Looking forward, the speed and success of Rwanda’s recovery will depend critically on the expansion of Rwanda’s social protection programs, boosting enterprises of all sizes, support to the agri-food system, and restoration of international trade.